SWIFT: An adaptive optics assisted I/z band integral field spectrograph - Tecza, M; Thatte, N; Clarke, F; Goodsall, T; Symeonidis, M (2006)
SWIFT is an adaptive optics assisted integral field spectrograph covering the I and z astronomical bands (0.7-1.0 mu m) at a spectral resolving power R <= 5000. At its heart is an all-glass image slicer with high throughput based on a novel de-magnifying design allowing a compact instrument. SWIFT profits from two recent developments: (i) the improved ability of second generation adaptive optics systems to correct for atmospheric turbulence in SWIFTS's bandpass, and (ii) the availability of CCD array detectors with high quantum efficiency at very red wavelengths. It is a dedicated integral field spectrograph, specifically built to address a range of interesting astrophysical questions. (c) 2005 Elsevier B.V. All rights reserved.